Synergistic anti-oxidative/anti-inflammatory treatment for acute lung injury with selenium based chlorogenic acid nanoparticles through modulating Mapk8ip1/MAPK and Itga2b/PI3k-AKT axis - Huizhen Xing; Xinwei Bai; Xiaoying Pei; Yuqi Zhang; Xueying Zhang; Shujun Chen; Dan Li; Bin Lv; Xiaoying Wang; Xiaoli Wu (Journal of Nanobiotechnology)
Abstract Oxidative stress and inflammatory dysregulation play crucial roles in pathogenesis of acute lung injury (ALI), and their cyclic synergy drives excessive inflammatory responses and further exacerbates ALI. Therefore, new effective strategies to treat ALI are urgently needed. Herein, a novel synergistic selenium based chlorogenic acid nanoparticle was developed to disrupt the cyclic synergistic effect between oxidative stress and inflammatory response in ALI. The chlorogenic acid, a polyphenol commonly found in herb, had been effectively conjugated with human serum albumin and coated on selenium nanoparticles (Se NPs) to create CHSe NPs. The CHSe NPs exhibited superoxide dismutase(SOD) like and glutathione peroxidase(GPX) like activities, effectively scavenging various types of reactive oxygen species (ROS), and inhibited the inflammatory response of macrophages. Additionally, with excellent biosafety, CHSe NPs exhibited superior therapeutic effects in ALI mice models in vivo, surpassing the performance of the clinic drug dexamethasone. They remarkably reduced ROS levels, and elevated the SOD and GPX enzyme activities in lung tissue to exert antioxidant effects. In addition, the CHSe NPs modulated the immune microenvironment of ALI by reversing M1 macrophage polarization, downregulating the expression levels of pro-inflammatory cytokines (IL-1β, IL-6, TNF-a), nitric oxide synthase (iNOS), and myeloperoxidase (MPO), and upregulating anti-inflammatory cytokine (IL-10) levels, thereby alleviating excessive inflammation and decreasing neutrophil infiltration. Further mechanistic research revealed that CHSe NPs directly acted on and modulated the expression of Mapk8ip1 and Itga2b, which were upstream proteins of MAPK signaling pathway and PI3K-Akt signaling pathway, therefore impeding the cyclic synergy between oxidative stress and inflammatory dysregulation. In summary, CHSe NPs synergistically exert antioxidant and anti-inflammatory effects by regulating the MAPK signaling pathway and PI3K-Akt signaling pathway, showing enormous potential in the treatment of ALI. Graphical Abstract